Burden of Thyroid and Lipid disorders among Elderly Depressed Patient: A cross sectional study in Nepal - Joshi, Rinku Gautam; Pandey, Arun Kumar; Sapkota, Nidesh; Kumar, Rajesh; Shah, Prashant; Maskey, Robin; Kattel, Vivek (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background and Objectives: Depression is common psychiatric illness among geriatric population however it remains underdiagnosed and undertreated. Majority of thyroid and lipid disorders are asymptomatic or have vague symptoms unless they land with emergency medical conditions. The burden of thyroid and lipid disorder are under reported in elderly population especially depressed one. The objective of the study was to measure the burden of thyroid and lipid disorders among Elderly Depressed Patient. Materials and methods: A hospital based cross-sectional study was conducted at BP Koirala Institute of Health Sciences, Dharan. All written consent patients more than 60 years of age with diagnosed of depression using ICD 10 criteria were screened for thyroid and lipid disorders as per hospital protocol. Those cases found to have thyroid and lipid disorders were reevaluated by physician for possibilities to rule out the false positive causes. Results: The prevalence of thyroid disorder and dyslipidemia was 29% and 62.7% respectively among 51 elderly depressed patient. Subclinical hypothyroidism was associated with 25% of the cohort. Hypertriglyceridemia (54.9%) was the most common form of lipid disorders followed by 47.1% increased total cholesterol level, 19.6% increased LDL level and 13.7% low HDL level. The presence of thyroid and lipid disorders were not significantly associated with types of depression (mild, moderate, severe and recurrent). Conclusion: Low threshold should be kept to screen subclinical hypothyroidism and dyslipidemia among geriatric depressed population due to alarming burden and adverse impact on quality of life and longevity.